O uso do blog como estratégia motivadora no processo de (multi) letramento digital nas aulas de língua estrangeira moderna (lem) - Santos, Kelly Cristine Martins dos Santos (2015)
English language lessons in the process of digital multiliteracy and it is inserted in the area of concentration of languages and technologies. This tool is presented as a way to stimulate students, from elementary school in a public school, whose rooms are not equipped for the use of technologies; so the students could only count with the lab they had at school. Initially, in order to meet the main goal of this work, namely, how to make use of the blog in English language lessons in the process of multiliteracy, theoretical biographic research was done, it was based on PCN's and in the new technologies, with support of some authors such as: Rojo (2013), Palfrey (2011). Castells (1999), Teruya (2006), Selber (2004), Lee (2002), Marchuschi (2005.2008), Levy (1999), among others. Moreover, to make the student came to the English language literacy a blog was created for pedagogical use in a task and used as support for students to post written productions done through reading of works previously selected by the author of this research. The results indicate that it is pertinent to use the blog as a pedagogical tool, and that the use of this feature is motivating for the students and can generate stimulating and creative productions.